Ecology of Self: woman’s self-discovery in Margaret Atwood’s Surfacing - Sandra Meškova (Baltic Journal of English Language, Literature and Culture)
The present paper discusses the problem of a woman’s self-perception in the environment degraded by patriarchal power relations and the pressures of contemporary consumer society, as depicted in Margaret Atwood’s novel Surfacing (first published in 1972). Atwood’s extensive and diverse writing is characterised by themes such as Canadian national and cultural identity, history, human rights, new humanism, ecological thinking, feminism, and issues of feminine identity. Women characters in Atwood’s writing are affected by the brutality, blindness, and deadlock created by imperial, patriarchal, and ethnocentric power structures. Nevertheless, they are portrayed as capable of creative self-expression and rational self-reflection. Consequently, texts depicting a woman’s self-discovery are of special significance in Atwood’s writing. This is particularly evident in Surfacing, where the heroine engages in introspection regarding her family’s genealogy, traces the imposed deformations of her experience, seeks the foundations of authentic feminine experience, and ultimately gains insight into her transformed perception of herself and her environment. The process of self-discovery in Atwood’s novel is analysed in the framework of the French feminist school of écriture féminine, the theoretical perspectives of Alice Jardine and Rita Felski, as well as cultural ecology.